ANALISIS KONTRIBUSI PEGADAIAN SYARIAH DALAM PENYALURAN KREDIT USAHA RAKYAT (KUR) TERHADAP PENGEMBANGAN UMKM DI KECAMATAN PURWOREJO KOTA PASURUAN - Rizky Veriansyah Frudin; Ifdlolul Maghfur; M. Dayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in promoting economic growth and creating employment opportunities. However, limited access to financing remains one of the main challenges faced by MSME actors in developing their businesses. This study aims to analyze the contribution of Islamic Pawnshop (Pegadaian Syariah) in distributing People's Business Credit (KUR) as a source of financing for MSMEs in Purworejo District, Pasuruan City. This research employed a qualitative method with a field research approach. Data were collected through observation, interviews, and documentation involving Islamic Pawnshop officers and 10 MSME beneficiaries of Sharia KUR financing. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that Islamic Pawnshop has made a significant contribution to improving MSMEs' access to capital through the Sharia KUR program. The financing provided was utilized to increase business capital, improve production capacity, and expand business activities. The Sharia KUR program also offers an easy financing application process and financing schemes that comply with Islamic principles. Nevertheless, several obstacles were identified, including low levels of Islamic financial literacy and limited program socialization among the community. Overall, Sharia KUR plays an important role in supporting MSME development and enhancing Islamic financial inclusion in Purworejo District, Pasuruan City